REASONS FOR THE INFLUENZA VACCINE REFUSAL AMONG PREGNANT WOMEN - Kovalenko , Kateryna; Malyk , Nataliia (Collection of scientific papers «ΛΌГOΣ», 2023)
Vaccination of pregnant women against influenza is a very relevant topic in family medicine. Due to immunological and physiological changes in pregnant women, the risk of susceptibility to infections of various genesis increases. Changes in the immune system are associated with hormones, cytokines and immune cells, as well as endometrial remodelling. Despite these changes, antibody response to influenza after natural infection and vaccination does not seem to differ between pregnant and not-pregnant women. A disease that occurs in the context of influenza can cause miscarriage, stillbirth, premature birth, and low birth weight. To prevent these complications, immunization of pregnant women is necessary, since influenza vaccination can act as direct protection for pregnant women and as passive immunity for infants under 6 months of age through maternal antibodies.